A study of the endocrine control of the prostate gland in relation to the etiology and the treatment of prostatic carcinoma and benign prostatic hyperplasia - Schoonees, Rikus (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.D.) -- University of Stellenbosch, 1971.